The relative contributions of domestic and foreign direct investments and exports to Malaysia's economic growth - Tang, Chor Foon; Tan, Eu Chye (World Scientific Publishing, 2015)
The objective of this study is to assess the roles of domestic direct investment, foreign direct investment and exports as catalysts of Malaysia's economic growth using cointegration and Granger causality test techniques. To address the dynamics in the growth relationships, the study also performs time-varying regression and variance decomposition analyses. It covers the quarterly sample period from 1991:Q1 to 2010:Q2. The econometric results suggest that all the three variables have a positive impact on economic growth and thus are catalytic to economic growth. However, the growth effect of domestic direct investment is more stable than that of the other two growth determinants. Contrary to earlier empirical studies, the variance decomposition analysis herein reveals that domestic direct investment is the most important determinant of growth in the long-run (L-R) compared to exports and foreign direct investment.